2002
DOI: 10.1016/s1470-0328(02)01478-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of outpatient hysteroscopy with saline infusion hysterosonography

Abstract: Objectives To establish the accuracy of saline infusion hysterosonography in diagnosing uterine pathology when compared with outpatient hysteroscopy. Design Prospective, parallel, blinded comparative study.Setting Outpatient hysteroscopy clinic in a large university teaching hospital.Population All women referred for outpatient hysteroscopy in a 15-month period.Interventions Women underwent saline infusion hysterosonography followed by flexible hysteroscopy. The ultrasonographer was blinded to the hysteroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…They consequently concluded that HYS exposed the patients to the same pelvic discomfort as TV-SHG, but had a better feasibility rate [29]. Contrary to this, Rogerson et al reported that TV-SHG had a high failure rate but had a lower pain score than HYS [37]. We had a 6.7% unsuccessful TV-SHG rate and no failed HYS application.…”
Section: Discussionmentioning
confidence: 82%
“…They consequently concluded that HYS exposed the patients to the same pelvic discomfort as TV-SHG, but had a better feasibility rate [29]. Contrary to this, Rogerson et al reported that TV-SHG had a high failure rate but had a lower pain score than HYS [37]. We had a 6.7% unsuccessful TV-SHG rate and no failed HYS application.…”
Section: Discussionmentioning
confidence: 82%
“…HSG has the added advantage in allowing an assessment of tubal patency simultaneously. However hysteroscopy in several studies has been shown to be more accurate than sonohysterography or hysterosalpingography (Cicenelli, Romano, Anastasio, Blasi, Parisi, & Galantino, 1995;Rogerson, Bates, Weston, & Duffy, 2002;Schwarzler et al, 1998). Additionally it has the benefit that hysteroscopic resection can be performed at the same time.…”
Section: Pre-operative Evaluationmentioning
confidence: 99%
“…SIS, in combination with an endometrium aspiration if necessary, can become the standard diagnostic procedure in women with abnormal uterine bleeding [15]. SIS is less painful, better tolerated by patients and less expensive than outpatient hysteroscopy [16][17][18]. The limitations of SIS include the cost (double TVS alone), the time to perform (an extra 5-10 min) and possible side effects, such as infection (very rare) and spilling of malignant cells [19].…”
Section: Saline Infusion Sonohysterographymentioning
confidence: 99%
“…All comparative studies concluded that SIS and hysteroscopy have similar accuracy in detecting endometrial lesions (polyps, fibroids and cancer) [16][17][18]29,30] but, in general, SIS is better tolerated by patients [16][17][18]. When assessing the cost-effectiveness of six strategies for the evaluation of menorrhagia (hormonal treatment; balloon ablation in all patients; TVS and therapeutic hysteroscopy; TVS, SIS and therapeutic hysteroscopy; SIS and therapeutic hysteroscopy; diagnostic hysteroscopy and therapeutic hysteroscopy) SIS was the procedure of first choice in the work-up of these women [31].…”
Section: The Optimal Diagnostic Algorithmmentioning
confidence: 99%